An Annotated Catalog of the Iranian Lygaeoidea (excluding Berytidae and Piesmatidae) (Hemiptera: Heteroptera: Pentatomomorpha) - Ghahari, Hassan; Moulet, Pierre (Zootaxa, 2012)
The Iranian fauna of the Lygaeoidea (excluding Berytidae and Piesmatidae) is summarized in this paper. In total, 9families, 7 subfamilies, 87 genera and subgenera, and 238 species and subspecies are listed from Iran. One species, Dieuches armatipes (Walker, 1872), is newly recorded from Iran.